1997
DOI: 10.1115/1.2841193
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Multi-Block CFD Code to Investigate the Impact of Geometry Modeling on Centrifugal Compressor Flow Field Predictions

Abstract: CFD codes capable of utilizing multi-block grids provide the capability to analyze the complete geometry of centrifugal compressors including, among others, multiple splitter rows, tip clearance, blunt trailing edges, fillets, and slots between moving and stationary surfaces. Attendant with this increased capability is potentially increased grid setup time and more computational overhead—CPU time and memory requirements—with the resultant increase in “wall clock” time to obtain a solution. If the increase in “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Chriss et al 3 and Harthaway and Wood 4 emphasized the importance of throughflow wake, which is largely fed by the tip clearance flow when the centrifugal impeller is throttled. Eisenlohr and Chladek 5 described the possibilities for optimizing passive tip clearance control by design features and suggested that transient expansion processes must be considered when using a thermal tip clearance control.…”
Section: Introductionmentioning
confidence: 99%
“…Chriss et al 3 and Harthaway and Wood 4 emphasized the importance of throughflow wake, which is largely fed by the tip clearance flow when the centrifugal impeller is throttled. Eisenlohr and Chladek 5 described the possibilities for optimizing passive tip clearance control by design features and suggested that transient expansion processes must be considered when using a thermal tip clearance control.…”
Section: Introductionmentioning
confidence: 99%
“…Also, with the availability of reliable experimental test data by AGARD 21 , researchers now have access to a plethora of data for validation of turbomachinery codes. Since then a number of three dimensional CFD codes capable of analyzing single and multiple blade passage turbomachinery flow have been developed by many researchers [22][23][24][25][26][27][28][29] .…”
Section: Computational Studies On Compressor Performancementioning
confidence: 99%
“…Ubaldi et al [9] concluded that turbulence kinetic energy is very high on the pressure side of the blade wake, where the jet has originated, and is lower on the suction side. Hathaway and Wood [10] used three-dimensional viscous code in their computational investigation of NASA low speed centrifugal compressor flow field. They concluded that increasing grid density in the tip gap by a factor of 6.5 resulted in no difference in predicted tip clearance overall flow nor in the chord wise distribution of the clearance flow.…”
Section: Introductionmentioning
confidence: 99%